Botanical origin of triterpenoids from Yucatecan propolis. (February 2019) - Herrera-López, Mercedes G.; Rubio-Hernández, Evelyn I.; Leyte-Lugo, Martha A.; Schinkovitz, Andreas; Richomme, Pascal; Calvo-Irabién, Luz M.; Peña-Rodríguez, Luis M.
Graphical abstract: Highlights: Mangiferolic acid, iso -mangiferolic acids and dammarenediol II in Yucatecan propolis. The resin of B. simaruba is a botanical source of triterpenes in propolis sample. Triterpenes in propolis sample not from the resin of local M.indica varieties. First report of dammarenediol II as a component of propolis. Abstract: Propolis is a resinous material produced by bees from plant exudates; the most common secondary metabolites found in propolis are poliphenolics with different biological activities. Nevertheless, to date, there are a number of reports describing the presence of triterpenoids in propolis. This work describes the isolation and identification of the triterpenoids mangiferolic acid (1 ), iso -mangiferolic acid (2 ), and dammarenediol II (3 ), together with a number of ubiquitous pentacyclic triterpenes, from the extract of a propolis sample collected in Yucatan, Mexico. While the cycloartanes1 and2 have been reported previously from propolis samples collected in Africa, Asia and South America, this is the first report of3 as a component in propolis. The botanical origin of3 and the pentacyclic triterpenes has been traced to the resin of Bursera simaruba, a tree commonly found in Yucatan peninsula. The results of this investigation confirm the close relationship between the flora surrounding the beehive and the chemical composition of propolis.